Associations of Face-to-Face and Instant Messaging Family Communication and Their Contents With Family Wellbeing and Personal Happiness Amidst the COVID-19 Pandemic - Gong, Wei Jie; Sit, Shirley Man Man; Wong, Bonny Yee Man; Wu, Socrates Yong Da; Lai, Agnes Yuen Kwan; Ho, Sai Yin; Wang, Man Ping; Lam, Tai Hing (Frontiers in Psychiatry, 2022)
Background Both face-to-face and instant messaging (IM) communication are important for families, but face-to-face communication has reduced amidst the COVID-19 pandemic. We examined the use and contents of both communication methods amidst the pandemic, their associations with family wellbeing and personal happiness, and the mediation effects of communication quality in Hong Kong Chinese adults. Methods This population-based online survey enrolled 4,921 respondents in May 2020, who reported (i) any face-to-face or IM family communication when the pandemic was severe; (ii) communication contents being classified as neutral, positive, supportive, and negative; and (iii) communication quality, family wellbeing and personal happiness (score 0–10). Associations of family wellbeing and personal happiness with communication methods and contents (no communication excluded) were examined using linear regressions (β), adjusting for each other, sex, age, socioeconomic status, and the number of cohabitants. Mediating effects of communication quality on these associations were examined. Prevalence estimates were weighted by sex, age, and education of the general population. Interactions of methods and contents were examined. Results Of 4,891 included respondents (female: 52.9%, 45–54 years: 37.7%, ≥65 years: 21.3%), 7.1% reported no communication, 12.7% face-to-face communication only, 26.7% IM only, and 53.4% both methods. More males and those at younger ages, had lower socioeconomic status, or fewer cohabitants showed no family communication or face-to-face only. More respondents reported neutral (83.1–99.3%) than positive (42.1–62.2%), supportive (37.5–54.8%), and negative (10.9–34.5%) contents despite communication methods. Communication quality was higher with both methods than IM only, face-to-face only, and no communication (scores: 6.7 vs. 4.5–6.6, all P ≤ 0.02). Better family wellbeing and personal happiness were associated with using IM only (adjusted βs: 0.37 and 0.48) and both methods (0.37 and 0.42) than face-to-face only, and positive (0.62 and 0.74) or supportive (0.45 and 0.46) contents (all P ≤ 0.001). Communication quality mediated 35.2–93.5% of these associations. Stronger associations between positive contents and family wellbeing showed in both methods and face-to-face only than IM only (P for interaction = 0.006). Conclusions We have first shown that, amidst the COVID-19 pandemic, family IM communication and positive and supportive contents may promote family wellbeing and personal happiness. People with no family communication may need assistance.